2000
DOI: 10.2134/agronj2000.9261211x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Nondestructive Techniques for Estimating Standing Crop in Shortgrass Plains

Abstract: placed on clipping, using it only for calibration and validation within trials. Nondestructive standing crop estimators are important for efficientThe canopy analyzer (CA) (LI-COR, Lincoln, NE) monitoring of native and agronomic systems. This study evaluated is a fast, nondestructive instrument that indirectly estiplot and pasture estimates of standing crop using LAI-2000, visual mates leaf area index (LAI; Welles and Norman, 1991). obstruction, canopy height, and weighted plate measurements. Research was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…Trotter et al [9] provides a review of these techniques which include visual assessment, pasture height recording devices, weighted plate meters, combinations of height and weighted plate meters, electrical capacitance probes, pendulum sensors as well as active optical sensors (AOS). Each of these techniques have their own advantages and disadvantages, however common issues included limited accuracy when dealing with spatially-variable phenology, morphology, species composition and green vs. dry fraction, e.g., [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trotter et al [9] provides a review of these techniques which include visual assessment, pasture height recording devices, weighted plate meters, combinations of height and weighted plate meters, electrical capacitance probes, pendulum sensors as well as active optical sensors (AOS). Each of these techniques have their own advantages and disadvantages, however common issues included limited accuracy when dealing with spatially-variable phenology, morphology, species composition and green vs. dry fraction, e.g., [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The height of the vegetation canopy has been used to measure plant volume and to infer biomass with success in the past [11,12,[22][23][24][25][26]. Of particular interest is the work by King et al [22], who reported that the sward height was linearly related to both the LAI and biomass over a range of 2 cm to 8 cm in two ryegrass dominant swards.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with a high density of biomass estimates generated by these techniques, transects can be made that account for uncertainties over heterogeneous canopies for remote sensing applications [12]. Reviews of in situ non-spectral methods pertaining to crops and rangelands can be found in [13][14][15]. These techniques involve: visual assessment (e.g., [16]), crop height (H) (e.g., [17]), fraction of absorbed photosynthetically active radiation (FAPAR) derived from a ceptometer, fraction of vegetation cover (FVC) derived from red-green-blue (RGB) band photographs (e.g., [18]), electronic capacitance probes (e.g., [19]), weighted discs (e.g., [20]) or pendulum sensors (e.g., [21]).…”
Section: Introductionmentioning
confidence: 99%
“…Systematic manual plant sampling has been used to analyse spatial distribution of dry matter yield and plant nutrient concentration and to predict its variability on grassland (Bailey et al 2001). This method requires great effort and expense to collect enough samples to accurately represent a pasture (Sharrow 1984;Hanna et al 1999;Ganguli et al 2000). Similar problems occur during the evaluation of large-size pasture yields, which require a high number of destructive samples to obtain sufficient accuracy of the estimate (Franca et al 2003).…”
Section: Introductionmentioning
confidence: 99%